2012
DOI: 10.1177/0883073812464270
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Epilepsy in Children With Cerebrovascular Disease

Abstract: Post-stroke seizures and epilepsy in children are a common but understudied complication. In this retrospective cohort study, the medical records of 65 children aged 0 to 18 years were analyzed to assess the risk of post-stroke seizures, detect the prevalence of post-stroke epilepsy, and ascertain which risk factors are associated with this condition in children. Forty-two patients (64.6%) had epileptic seizures following stroke (35 early, 7 late-onset), with most (78.5%) occurring in the first 24 hours. Ninet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 25 publications
5
18
0
2
Order By: Relevance
“…Morais et al (5) and Yang et al (14) found a significant association between late post-stroke seizures and epilepsy in children after ischemic stroke similar to our study. These studies agree that late post-stroke seizure was a risk factor for post-stroke epilepsy.…”
Section: Epilepsysupporting
confidence: 80%
See 4 more Smart Citations
“…Morais et al (5) and Yang et al (14) found a significant association between late post-stroke seizures and epilepsy in children after ischemic stroke similar to our study. These studies agree that late post-stroke seizure was a risk factor for post-stroke epilepsy.…”
Section: Epilepsysupporting
confidence: 80%
“…These similar pathophysiologic mechanisms are cellular biochemical dysfunction for early post-stroke seizures and epileptogenic gliotic scarring for late post-stroke seizures (15) . This high risk of post-stroke epilepsy has been also observed in the cases with late post-stroke seizures investigated in other studies (3,5,14) and furthermore this risk is higher than that reported for the general population experiencing their first unprovoked seizures (16) . Therefore, Dhanuka et al (17) also made a conclusion that early post-stroke seizures were rather common, did not recur and could not be treated with AEDs.…”
Section: Epilepsymentioning
confidence: 69%
See 3 more Smart Citations